Iowa Birdline update, May 8, 1990 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for May 8, 1990. Highlights of the update include sightings of two White-faced Ibis, a lingering Common Loon, a late Rough-legged Hawk, and nesting Cooper's Hawks. Also of note was the recovery of an injured Barn Owl and the presence of several species of shorebirds. Epson - sheet feed/flatbed